VD_FINDINFO Décision / 2012 / 632 vom 23. Juli 2012 - VD Tribunal cantonal (2012)
NON-LIEU, FRAIS DE LA PROCÉDURE, DÉPENS | 319 CPP (CH), 395 let. b CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)